Solids Turn into Liquids-Liquid Eutectic Systems of Pharmaceutics to Improve Drug Solubility - Mafalda C. Sarraguça; Paulo R. S. Ribeiro; Cláudia Nunes; Catarina Leal Seabra (MDPI AG, 2022)
The low solubility of active pharmaceutical ingredients (APIs) is a problem in pharmaceutical development. Several methodologies can be used to improve API solubility, including the use of eutectic systems in which one of the constituents is the API. This class of compounds is commonly called Therapeutic Deep Eutectic Systems (THEDES). THEDES has been gaining attention due to their properties such as non-toxicity, biodegradability, and being non-expensive and easy to prepare. Since the knowledge of the solid liquid diagram of the mixture and the ideal eutectic point is necessary to ascertain if a mixture is a deep eutectic or just a eutectic mixture that is liquid at ambient temperature, the systems studied in this work are called Therapeutic Liquid Eutectic Systems (THELES). Therefore, the strategy proposed in this work is to improve the solubility of chlorpropamide and tolbutamide by preparing THELES. Both APIs are sulfonylurea compounds used for the treatment of type 2 diabetes mellitus and have low solubility in water. To prepare the THELES, several coformers were tested, namely, tromethamine, L(+)-arginine, L-tryptophan, citric acid, malic acid, ascorbic acid, and p-aminobenzoic acid, in molar ratios of 1:1 and 1:2. To improve viscosity, water was added in different molar ratios to all systems. THELES were characterized by mid-infrared spectroscopy (MIR), and differential scanning calorimetry. Their viscosity, solubility, and permeability were also determined. Their stability at room temperature and 40 °C was accessed by MIR. Cytocompatibility was performed by metabolic activity and cell lysis evaluation, according to ISO10993-5:2009, and compared with the crystalline APIs. THELES with TRIS were successfully synthesized for both APIs. Results showed an increased solubility without a decrease in the permeability of the APIs in the THELES when compared with the pure APIs. The THELES were also considered stable for 8 weeks at ambient temperature. The cells studied showed that the THELES were not toxic for the cell lines used.